Sufficiency Thinking Thailand's gift to an unsustainable world - Avery, Gayle C. (Allen & Unwin, 2016)
The first systematic account of the powerful decision-making framework which is being applied across all areas of life in Thailand to build a fair, resilient and sustainable economy and society
Description based on publisher supplied metadata and other sources